Reconstructing ancient Korean history : the formation of Korean-ness in the shadow of history - Xu, Stella (Lexington Books, 2016)
"This book examines the historiography of ancient Korea and its relationship to the construction of Korean national identity through a critical and comparative analysis of Chinese and Korean primary sources. It also analyzes the ways in which Korean politics and culture have shaped and been affected by historical narratives"--Provided by publisher